PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TTW (THINK-TALK-WRITE) DALAM MENINGKATKAN HASIL BELAJAR SISWA - edi kurniawan (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2018)
This research aims to find out the increase student learning outcomes on the subject of solubility and solubility product through the application of cooperative learning type of Think-Talk-Write (TTW) of grade XI science at Senior High School 10 Pekanbaru. This type of research is experimental research with data retrieval time from the date of 18 May to 1 June 2013. The samples in this research are students of class XI IPA2 as experimental class and class XI IPA1 as control class selected after conducting test of homogeneity. Techniques of data collection in this research was to test the homogeneity as initial data on the material previously ie Salt Hydrolysis, documentation, observations, pretest and posttest as final data. Final data analysis in this research using test "t". From the calculations, t count = 4.59 at significant level of 5% obtained t table = 1.66, showing that t count≥ t table so that Ho is rejected and Ha accepted. The magnitude of the average normalized gain <N-GAIN> student learning outcomes experimental class was 0.75 which includes high category, and for the control class is 0.70 which included a middle category. Based on the results of these data analysis, it is concluded that an increase in learning outcomes on the subject of solubility and solubility product with the application of cooperative learning model type of Think-Talk-Write (TTW) of grade XI science at Senior High School 10 Pekanbaru